What is driving the pollution abatement expenditure behavior of manufacturing plants in Korea? - Aden, J.; Ahn, Kyu-Hong; Rock, M.T. (1999)
Relatively little is known about the environmental behavior of manufacturing plants in Korea. We address this lacuna by reporting the results of a survey designed to assess the scope of plant-level pollution abatement expenditures, the intensity of plant-level exposure to regulatory actions and community pressure, and the impact of each on abatement expenditures. Survey results reveal substantial expenditures on pollution abatement and significant exposure to regulatory actions and community pressure. Two-stage least squares (TSLS) estimation of a responsive regulation type model suggests that Korean regulators may be engaged in responsive regulation that works and that plant characteristics (size, productivity, and ownership) and community pressure also affect plant-level abatement expenditures.
Keywords: abatement cost; manufacturing; pollution control; Korea